NAD+ supplementation rejuvenates aged gut adult stem cells. Issue 3 (27th March 2019) - Igarashi, Masaki; Miura, Masaomi; Williams, Eric; Jaksch, Frank; Kadowaki, Takashi; Yamauchi, Toshimasa; Guarente, Leonard
Abstract: The tissue decline due to aging is associated with the deterioration of adult stem cell function. Here we show the number and proliferative activity of intestinal stem cells (ISCs) but not Paneth cells decline during aging, as does ISC function assessed ex vivo. Levels of SIRT1 and activity of mTORC1 also decline with aging. The treatment with the NAD(+) precursor nicotinamide riboside (NR) rejuvenates ISCs from aged mice and reverses an impaired ability to repair gut damage. The effect of NR is blocked by the mTORC1 inhibitor rapamycin or the SIRT1 inhibitor EX527. These findings demonstrate that small molecules affecting the NAD/SIRT1/mTORC1 axis may guide a translational path for maintenance of the intestine during aging.